On the move to meaningful internet systems : OTM 2016 Workshops : Confederated International Workshops: EI2N, FBM, ICSP, Meta4eS, and OTMA 2016, Rhodes, Greece, October 24-28, 2016, Revised selected papers /: OTM 2016 Workshops : Confederated International Workshops: EI2N, FBM, ICSP, Meta4eS, and OTMA 2016, Rhodes, Greece, October 24-28, 2016, Revised selected papers. (2017) - Unknown
No abstract available